Relative expression of genes related to volatile organic compounds in non-climacteric and climacteric melons - Kamila Karoline de Souza Los; Michelle Orane Schemberger; Marilia Aparecida Stroka; Calistene Aparecida Pinto; Caroline Weigert Galvão; Rafael Mazer Etto; Amanda Regina Godoy Baptistão; Ricardo Antonio Ayub (Acta Scientiarum: Agronomy, 2024)
Melon (Cucumis melo L.) is an important species in the cucurbit family with a large economic importance in the world. Two melon cultivars commercially important in Brazil are ‘Yellow’ and ‘Gaúcho’. In addition to their economic importance, these two cultivars display phenotypic differences in aroma, a major trait determining fruit quality. Volatile organic compounds (VOCs) impart the different aroma found in this fruit and their biosynthesis is associated with fatty acid and amino acid metabolism. Using RT-qPCR techniques, the expression of seven genes (CmLOX9, CmLOX18, CmBCAT1, CmArAT1, CmPDC1, CmADH1, and CmAAT1) was determined during ripening. The lipid pathway played a strong role in determining aroma composition in non-climacteric ‘Yellow’ melons. Most volatiles decreased during ripening, explaining the non-aromatic characteristic of this cultivar. In climacteric ‘Gaúcho’ melons, the amino acid pathway was the main one related to the biosynthesis of esters, which contribute to the aroma of this cultivar. Volatile products of the branched-chain amino acid pathway correlated with CmADH1 and CmAAT1 expression, demonstrating their role in volatile synthesis in this climacteric melon cultivar. In addition, CmPDC1 contributes to the formation of aldehydes at the beginning of this pathway.